Mas Signaling Potentiates Neutrophil Extracellular Traps Formation Induced by Endothelial Cells Derived S1P in Mice with Acute Liver Failure - Bo Yang; Shuai Chen; Xiaoqi Xia; Ziwen Tao; Chun Liu; Shanshan Li; Shuo Zhang; Jiali Huang; Lu Xia; Wenqiang Quan; Changqing Yang; Jing Li (Advanced Science)
Abstract Mas, a newly identified G‐protein‐coupled receptor, is prevalent in myeloid‐derived immune cells and plays a key role in inflammation. This study investigates Mas signaling and neutrophil extracellular traps (NETs) in acute liver failure (ALF), aiming to elucidate their mechanisms. Male Mas1−/− and wild‐type mice, aged 6–8 weeks, receive intraperitoneally injected with lipopolysaccharide (LPS)/D‐galactosamine (D‐Gal) (L/G) to study NETs formation. Hepatic Mas expression increases in WT‐L/G mice, whereas systemic Mas1 knockout significantly reduces L/G‐induced NETs and hepatotoxicity. Antibiotics treatment and co‐housing (Mas1−/−‐L/G and WT‐L/G mice) experiments show that gut flora influences the disease phenotype in Mas1−/−‐L/G mice. Fecal metabolite analysis suggests that mice may be protected by reduced deoxycholic acid (DCA) production in Mas1−/− activated hepatic farnesoid X receptor (FXR), suppressing sphingosine‐1‐phosphate (S1P)‐dependent NETs. Additionally, Mas1−/− also activates the FXR‐S1P‐NETs axis in the liver by inhibiting SHP2. Single‐cell sequencing shows decreased interaction between endothelial cells and Cldn1+CD177+ senescent neutrophils through Col4a1‐CD44. This inhibits S1P‐induced Raf signaling pathway activation and NETs formation. Mas signaling significantly impacts NETs formation, highlighting its potential as an anti‐inflammatory therapeutic target for ALF.